2020
DOI: 10.1371/journal.pone.0230897
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis after resection of single large hepatocellular carcinoma: Results from an Asian high-volume liver surgery center

Abstract: Background & aims In 2012, the Barcelona Clinic Liver Cancer (BCLC) system designated a single large hepatocellular carcinoma (SLHCC) (>5 cm) as BCLC stage A rather than stage B. However, a recent study from western countries reported that prognosis following liver resection (LR) among patients with SLHCC was similar to that among patients with BCLC stage B. We aim to evaluate the prognosis following LR among patients with SLHCC from an Asian high-volume liver surgery center. Methods Patients who underwent cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(45 reference statements)
3
5
0
Order By: Relevance
“…In addition, surgical resection has also been questioned, as a single large tumor is always associated with a high recurrence rate and worse survival. However, consistent with the current study, more and more studies have demonstrated improved survival of these patients after surgical resection vs. TACE or palliative treatments [ 26 28 ]. Taken together, data from the current study also strongly advocate surgical resection as the first-line treatment for patients with a single HCC >5 cm.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, surgical resection has also been questioned, as a single large tumor is always associated with a high recurrence rate and worse survival. However, consistent with the current study, more and more studies have demonstrated improved survival of these patients after surgical resection vs. TACE or palliative treatments [ 26 28 ]. Taken together, data from the current study also strongly advocate surgical resection as the first-line treatment for patients with a single HCC >5 cm.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies reported that patients receiving SR had better OS rates than those receiving TACE in BCLC stage B HCC patients 8,25 . Recent, several studies showed survival benefit of liver resection for BCLC stage B HCC patients 16,17,23,24,26–29 . Moreover, our study is also consistent with previous study demonstrating that SR was significantly associated with better OS and PFS than TACE 12 …”
Section: Discussionsupporting
confidence: 91%
“…A significant proportion of patients in the present study underwent LR because HBV is the leading etiology of HCC in Taiwan and a higher proportion of the patients had HBV–associated non-cirrhotic HCC. Our previous study found that around 60% of patients with HCC who underwent LR were non-cirrhotic [ 26 ]. Major liver resections can be performed with low rates of major complications in non-cirrhotic patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%